Обзор методологических подходов исследования «совладающего копинг-поведения» и «денег» (The Journal of Psychology and Sociology, 2019)
In psychology the “coping behavior” is studied more recently. “Money”, psychologically speaking of its influence on person, despite its daily significance and antiquity, has not been studied at all. Monetary relations in society have long gone beyond the economy, representing a stable factor of psychological pressure and regulation of social relations in society. “Money” or in particular their amount, affect the behavior of its creator in completely different ways, depriving it of its humanity, will, mind and adequacy, which is confirmed by dry figures of a world statistics that more than 90% of criminal crimes in the world (robberies, murders , slavery, fraud, raiding, etc.) are associated with money or its equivalent. In addition to criminal statistics, the negative impact of “money” on a person is supported by impressive numbers of “credit” or “monetary” suicide cases, mental disorders, stress and other life-threatening psychosomatic and other illnesses. It is in that connection that the research topic “The value-semantic aspects of young people’s attitude towards money with different styles of coping behavior” is relevant more than ever, given that the person’s life, health, career, family welfare and the development of society depend directly on his or her behavior. In this article the main aspects of classical methodology are considered; special methodological guidance of the far abroad scientists and specific difficulties in choosing the methodology for conducting research on “coping behavior” and “money.” The impact of money on human behavior, its vital values and other social aspects are very relevant. The global financial crisis on the one hand and economy of abundance on the other put a person in a tricky situation of a difficult choice almost every day. Identifying the psychological aspect of the impact of money on a person and his traditional values in the form of family, love and friendship, binds in a single complex a set of completely different scientific directions and specialties that have great applied, and therefore practical importance for the society as a whole and for each individual particularly.Key words: methodology, psychology, money, coping, coping behavior.